2019
DOI: 10.1103/physrevlett.122.057601
|View full text |Cite
|
Sign up to set email alerts
|

Robust Coupling between Structural and Electronic Transitions in a Mott Material

Abstract: The interdependences of different phase transitions in Mott materials are fundamental to the understanding of the mechanisms behind them. One of the most important relations is between the ubiquitous structural and electronic transitions. Using IR spectroscopy, optical reflectivity and x-ray diffraction we show that the metal-insulator transition (MIT) is coupled to the structural phase transition in V2O3 films. This coupling persists even in films with widely varying transition temperatures and strains. Our f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
71
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 67 publications
(84 citation statements)
references
References 55 publications
13
71
0
Order By: Relevance
“…4, we extract the volume fraction of the rutile metallic phase based on the responses at 529 eV and 530.5 eV independently and assuming that only the rutile phase is generated, in a similar approach to Ref. [13]. In Fig.…”
Section: Electronic and Structural Changes At Thresholdmentioning
confidence: 99%
See 1 more Smart Citation
“…4, we extract the volume fraction of the rutile metallic phase based on the responses at 529 eV and 530.5 eV independently and assuming that only the rutile phase is generated, in a similar approach to Ref. [13]. In Fig.…”
Section: Electronic and Structural Changes At Thresholdmentioning
confidence: 99%
“…This can occur even in the comparatively simple case of equilibrium measurements. For instance, comparing near-field imaging and x-ray diffraction methods gave rise to the claim that the electronic and structural phase transitions in the related vanadium compound V 2 O 3 are decoupled in temperature [12], while later measurements showed this to be an artifact arising from comparing techniques [13]. The equilibrium transition is similarly controversial for VO 2 , where approaches that combine different techniques have suggested that the equilibrium transitions can be decoupled [14], while techniques that can probe both aspects of the phase transition simultaneously show they are not [15].…”
Section: Introductionmentioning
confidence: 99%
“…Various mechanisms have been investigated and employed to realize tunable nanophotonic and metasurface platforms. These include the transition from nematic to isotropic phases in liquid crystals [31], [32], amorphous to crystalline phase change in GeSbTe (GST) [54], [76], [77] and metal─insulator transitions (MIT) in prototypical strongly correlated materials such as vanadium dioxide (VO 2 ) [67], [78]- [82] and V 2 O 3 [83], [84].…”
Section: Phase Transition Materialsmentioning
confidence: 99%
“…The strong coupling effects between the degree of freedom of charge, spin, and lattice determine the IMT behaviors of VO 2 . However, it is disputed whether electron correlation (Mott transition) or electron–phonon interaction (Peierls transition) triggers such IMT . Distinguishing SPT and IMT also remains a challenge in VO 2 .…”
Section: Introductionmentioning
confidence: 99%